Effect of Credit Ratings on Airport Financing and Management - KATO, Kazusei (Institutional Knowledge at Singapore Management University, 2010)
This paper analyzes the effect of airport ownership structure on management efficiency as reflected through their credit ratings. A game-theoretical model is proposed to examine the role of credit ratings in mitigating the moral hazard problem of public-owned airports. The analytical results derived from the model are then used to supplement a supporting case study. Notwithstanding the fact that the less competitive environment of a public-owned entity and its credit ratings might bring some welfare loss , this research concludes that public-owned airports have some advantages.